2019
DOI: 10.1093/zoolinnean/zlz112
|View full text |Cite
|
Sign up to set email alerts
|

Palaeobiodiversity of crocodylomorphs from the Lourinhã Formation based on the tooth record: insights into the palaeoecology of the Late Jurassic of Portugal

Abstract: Crocodylomorphs were a diverse clade in the Late Jurassic of Portugal, with six taxa reported to date. Here we describe 126 isolated teeth recovered by screen-washing of sediments from Valmitão (Lourinhã, Portugal, late Kimmeridgian–Tithonian), a vertebrate microfossil assemblage in which at least five distinct crocodylomorph taxa are represented. Ten morphotypes are described and attributed to five clades (Lusitanisuchus, Atoposauridae, Goniopholididae, Bernissartiidae and an undetermined mesoeucrocodylian). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Analysis of the osteological record reveals that crocodylomorphs were diverse in the Late Jurassic ecosystems of the Lusitanian Basin, with six different taxa reported so far (Krebs & Schwarz 2000; Puértolas‐Pascual & Mateus 2020; Guillaume et al 2020). The latter authors recently reported five different clades ( Lusitanisuchus , Atoposauridae, Goniopholididae, Bernissartiidae and an undetermined mesoeucrocodylian) in the same formation (Praia da Amoreira‐Porto Novo Fm.)…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Analysis of the osteological record reveals that crocodylomorphs were diverse in the Late Jurassic ecosystems of the Lusitanian Basin, with six different taxa reported so far (Krebs & Schwarz 2000; Puértolas‐Pascual & Mateus 2020; Guillaume et al 2020). The latter authors recently reported five different clades ( Lusitanisuchus , Atoposauridae, Goniopholididae, Bernissartiidae and an undetermined mesoeucrocodylian) in the same formation (Praia da Amoreira‐Porto Novo Fm.)…”
Section: Discussionmentioning
confidence: 96%
“…Finally, the palaeoecology of both groups should be analysed. Many of the crocodylomorphs identified in the formation are freshwater crocodylomorphs that would have been well adapted to an aquatic lifestyle (Guillaume et al 2020; Wilberg et al 2020). By contrast, although pterosaurs lived close to marine and freshwater habitats, there are doubts about how they could have produced the traces since they would have been partially constrained to remain at the surface of the water (Hone & Henderson 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teeth attributed to atoposaurids had crowns with mesial and distal carinae and were ornamented with apicobasal ridges. These also showed a wide morphological variability comprising conical, lanceolate, and broad leaf-shaped crowns in relation to the position in the dental arcade (e.g., [35,36]). Osteichthyans are scarce, but remains have been identified in addition to scales, such as some lanceolated teeth with smooth carinae belonging to Amiiformes indet.…”
Section: Screen-washing Subsamplingmentioning
confidence: 99%
“…This study not only addresses the palaeobiodiversity of the Lourinhã crocodylomorph fauna, but also explores their ecological relationships. Based on the different dental morphologies, four distinct feeding behaviours (durophagous, "insectivorous", hypercarnivorous and generalist) are hypothesized (Guillaume et al, 2020).…”
mentioning
confidence: 99%